2020
DOI: 10.1186/s13018-020-01844-x
|View full text |Cite|
|
Sign up to set email alerts
|

The Toll-like receptor ligand, CpG oligodeoxynucleotides, regulate proliferation and osteogenic differentiation of osteoblast

Abstract: Background: This study aimed to investigate the regulation of CpG oligodeoxynucleotides (ODNs) on proliferation and osteogenic differentiation of MC3T3 cells. Methods: The laser co-focusing and flow cytometry assay were employed to detect cell uptake of CpG ODN 2006. Twelve ODNs were sythesized, and their effects on proliferation and differentiation were detected by MTT and alkaline phosphatase (ALP) activity assay. Flow cytometry assay was used to examine the regulation of CpG ODN on cell cycle. Quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A 27-base cytosine (C)-rich ODN designed from the human mitochondrial genome, named MT01 ([ACC CCC TCT] 3 ), was initially identified as an immunosuppressive ODN that inhibits the proliferation of human peripheral blood mononuclear cells [ 18 ]. Intriguingly, MT01 promoted the proliferation and differentiation of the human osteoblast-like cell line MG63 [ 19 ], rat bone marrow mesenchymal stem cells [ 20 ], and murine osteoblast cell line MC3T3-E1 [ 21 ] by upregulating Runx2 phosphorylation via activation of the ERK/MAPK pathway [ 22 ]. Thus, MT01 treatment reduced alveolar bone loss in rat periodontitis in vivo [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 27-base cytosine (C)-rich ODN designed from the human mitochondrial genome, named MT01 ([ACC CCC TCT] 3 ), was initially identified as an immunosuppressive ODN that inhibits the proliferation of human peripheral blood mononuclear cells [ 18 ]. Intriguingly, MT01 promoted the proliferation and differentiation of the human osteoblast-like cell line MG63 [ 19 ], rat bone marrow mesenchymal stem cells [ 20 ], and murine osteoblast cell line MC3T3-E1 [ 21 ] by upregulating Runx2 phosphorylation via activation of the ERK/MAPK pathway [ 22 ]. Thus, MT01 treatment reduced alveolar bone loss in rat periodontitis in vivo [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the relationship between TLRs and BMP-2 remains unclear. It has been observed that other ligands for TLRs can activate osteoblasts [ 48 ]. Conversely, when a TLR inhibitor is applied to grafts, it inhibits bone regeneration [ 49 ].…”
Section: Studies On Sericin In Bone Graftingmentioning
confidence: 99%
“…To date, most gene therapy for periodontitis has focused on bone regeneration (215)(216)(217). There is still little research on the immune microenvironment, but some of the existing studies show good application prospects (214).…”
Section: Gene Therapymentioning
confidence: 99%